Protection Debugging of Digitized Substation Based on IEC 61850 - YANG Mei; ZHOU Xi-chao; LEI Yan-xia; CAI Li (Gong-kuang zidonghua, 2010)
The paper introduced main characteristics of digitized substation based on IEC 61850 and some changs of protection debugging for substation caused by application of IEC 61850 standard, discussed methods of protection debugging of digitized substation based on IEC 61850, and breifly analyzed selection of testing instruments, connection of testing systems and operation of debugging method.